Differences of Brain volume, Hippocampal volume, Cerebrovascular risk factors and APOE4 among MCI subtypes - He, Jing (2009)
OBJECTIVES: To evaluate demographics, magnetic resonance imaging (MRI) measures, and Vascular risk among mild cognitive impairment (MCI) subtypes. DESIGN: Cross-sectional study. SETTING: Both clinics and the community. PARTICIPANTS: A total of 153 subjects with MCI, 218 cognitively normal older individuals (controls), and 68 patients with Alzheimer disease. MAIN OUTCOME MEASURES: Classification of subjects with MCI according to current subtype diagnostic convention based on neuropsychological performance, estimates of vascular risk based on medical history, research MRI unless there was a specific contraindication, and apolipoprotein E genotype. RESULTS: Of the 153 subjects with MCI, 65 were diagnosed with amnestic single-domain, 46 with amnestic multiple-domain, 27 with nonamnestic single-domain, and 15 with nonamnestic multiple-domain MCI. Analyses of control, MCI, and Alzheimer disease cases revealed significant differences in brain and hippocampal volumes between each group. Post hoc analyses of MRI measures among the MCI subtypes found that patients with amnestic single-domain MCI had significantly less brain atrophy and that hippocampal volume differed significantly from controls for the 2 amnestic forms of MCI. Apolipoprotein E genotype prevalence was significantly greater in the amnestic and nonamnestic subtypes of MCI. Conversely, the nonamnestic subtypes were more likely to have increased vascular risk and to be African American. CONCLUSIONS: Amnestic forms of MCI appear to have demographic, genetic, and MRI findings suggestive of Alzheimer disease pathology, whereas the nonamnestic forms of MCI have findings suggestive of vascular disease. Importantly, however, all subjects with MCI showed evidence of brain injury, and the biological differences among subtypes are relatively subtle beyond the memory vs nonmemory groupings.